PERAN KEPALA KELUARGA DALAM MENGATASI KEMALASAN BELAJAR ANAK PERSPEKTIF MANAJEMEN KONFLIK - Muhammad Iqbal; M.Hafid Mahmudi (Judge : Jurnal Hukum, 2026)
This study aims to analyze the strategies employed by heads of families in overcoming children’s learning laziness and the application of conflict management approaches in creating a positive and supportive learning environment. This research adopts a qualitative method with a descriptive approach. Data were collected through in-depth interviews with six heads of families in Bumi Tegal Besar Housing Complex, Jember Regency, selected purposively. Data analysis was conducted through data reduction, data presentation, and systematic conclusion drawing. The findings indicate that children’s learning laziness is influenced by internal factors such as low interest and boredom, as well as external factors including gadget use and environmental influence. To address this issue, heads of families predominantly apply dialogical and participatory strategies by involving children in learning arrangements and emphasizing emotional communication. The dominant conflict management approach is listening first and then evaluating, which reflects collaborative and compromising styles. This approach effectively reduces learning-related tension, balances discipline and flexibility, and fosters a conducive learning environment. Moreover, spousal support and parental partnership play a crucial role in strengthening conflict management practices within the family.